DNA Micro‐Disks for the Management of DNA‐Based Data Storage with Index and Write‐Once–Read‐Many (WORM) Memory Features. Issue 37 (29th July 2020) - Choi, Yeongjae; Bae, Hyung Jong; Lee, Amos C.; Choi, Hansol; Lee, Daewon; Ryu, Taehoon; Hyun, Jinwoo; Kim, Seojoo; Kim, Hyeli; Song, Suk‐Heung; Kim, Kibeom; Park, Wook; et al.
Abstract: DNA‐based data storage has attracted attention because of its higher physical density of the data and longer retention time than those of conventional digital data storage. However, previous DNA‐based data storage lacked index features and the data quality of storage after a single access was not preserved, obstructing its industrial use. Here, DNA micro‐disks, QR‐coded micro‐sized disks that harbor data‐encoded DNA molecules for the efficient management of DNA‐based data storage, are proposed. The two major features that previous DNA‐based data‐storage studies could not achieve are demonstrated. One feature is accessing data items efficiently by indexing the data‐encoded DNA library. Another is achieving write‐once–read‐many (WORM) memory through the immobilization of DNA molecules on the disk and their enrichment through in situ DNA production. Through these features, the reliability of DNA‐based data storage is increased by allowing selective and multiple accession of data‐encoded DNA with lower data loss than previous DNA‐based data storage methods. Abstract : DNA micro‐disks, QR‐coded micro‐sized disks that harbor data‐encoded DNA molecules for the efficient management of DNA‐based data storage are proposed. Using these DNA micro‐disks, data items can be efficiently accessed by indexing the data‐encoded DNA library and write‐once–read‐many (WORM) memory can be demonstrated through in situ DNA production on the DNA micro‐disks.